Impoliteness Used In Command By Characters In One Piece Comic Strip - Hartono, Muh. Farid, Agus Wijayanto, Ph.D, Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
This research using theory of Impoliteness done by Culpeper (1996). The research is aimed at describing types of Impoliteness Strategies, the influence of the Gender assumption, Familiarities, and the Social Levels in using Impoliteness Aspects in One Piece Comic Strip. This research applied descriptive qualitative method. The data are a comic strip by Eiichiro Oda entitled "One Piece". The way to collect data is using docummentation method. The data analyze are impoliteness strategies found in the comic strip "One Piece" and combines by describing gender differences, familirities of characters, and social levels. The result show that 1) there are 56.92 % or 74 data of positive impolitness, 36,15 % or 47 data of negative impoliteness, 36.15 % or 9 data of bald on record impoliteness, 0.76 % or 1 data of sarcam or mock politeness, and no data found in withhold politeness. 2) there are male and female spakers existed by using impoliteness strategies in this comic. 3) there are relationship among close, familiar, and unfamiliar relationship in this comic. The last is 4) the social levels, are equal, lower, and higher status.